A cross-sectional survey study on the correlation analysis of nutritional status and intestinal flora in patients with esophageal cancer - LiYa, Li; XinSheng, Zhang; Xiang, Huang; Zhao, Liu; Lu, Liu; XiuMing, Lv; Ye, Li; Jing, Chen; KeMing, Zhang; HongChi, Wang; Jing, Xia; Yang, Cong; et al. (Frontiers in Nutrition, 2024)
The objective of this study is to examine the nutritional status of individuals diagnosed with esophageal cancer, and to compare the nutritional indicators and intestinal flora between malnourished and well-nourished patients. The findings aim to contribute to the early prevention of malnutrition and the development of interventions targeting the intestinal flora in the treatment of esophageal cancer. An 80-patient sample of hospitalized individuals with esophageal cancer was selected from the radiotherapy department of our hospital between July 2021 and July 2022 for the purpose of evaluating NRS2002 scores and PG-SGA scores. This cross-sectional analysis aimed to examine the disparities in dietary nutrient intake, blood indicators, body composition, and fecal intestinal flora between malnourished and well-nourished patients with esophageal cancer. Additionally, a random selection of 40 cases was made to predict and analyze the relationship between intestinal flora and malnutrition. The conclusion of this study showed that esophageal cancer patients are more likely to be malnourished. The nutritional status of these patients is closely linked to the intakes of carbohydrates and fiber, albumin levels, inflammation levels, and lean body mass. Furthermore, the composition of the patient's intestinal flora plays a significant role in their nutritional well-being. Consequently, modulating the intestinal flora holds promise as a potential therapeutic approach for addressing malnutrition in esophageal cancer patients.